The Tourist Accommodation Infrastructure in the Mountainous and Marginal Contact Area of Mureș County - The Decisive Factor for the Elaboration of Sustainable Tourism Strategies - Andreea-Maria CRĂCIUN; Ștefan DEZSI; Florin POP; Judith NYULAS (Studia Universitatis Babeş-Bolyai: Geographia, 2025)
The Tourist Accommodation Infrastructure in the Mountainous and Marginal Contact Area of Mureș County - the Decisive Factor for the Elaboration of Sustainable Tourism Strategies. The analysis of the tourist accommodation infrastructure of the mountainous and marginal contact area of Mureș County is part of a larger study on tourism in the area. This paper has analyzed statistical data on tourism structures with accommodation functions and their accommodation capacity in 2024 from a triple perspective: based on data provided by the National Institute of Statistics (INS), the Ministry of Economy, Entrepreneurship and Tourism (MEDAT) and, last but not least, data obtained through our own investigation. The purpose of this work is to provide a clear and close picture of the existing tourist accommodation units in the reference area so that the results obtained can be used to carry out the following sequences of the study and to foreshadow tourism development strategies in the area. As in the case of other economic activities, tourism has had periods of decline, stagnation, and positive evolution over the years, determined either by political, natural, social or economic causes.